Historia życia i działalności Benedykta Dybowskiego – wielkiego zoologa, lekarza, antropologa, działacza niepodległościowego, zesłańca syberyjskiego: The Story of Life and Work of Benedykt Dybowski – an Eminent Zoologist, Physician, Polish Independence Activit, Siberian Deportee - Garbula, Joanna Maria (Przegląd Wschodnioeuropejski, 2019)
This article is dedicated to Benedykt Dybowski, his patriotic, social and professional life, first at university, and then in exile, working in Kamchatka. The references for this review consist of archived documents such as scientific dissertations and diaries authored by Dybowski, and articles and books written about him. This article is an attempt to show Dybowski’s outstanding scientific output and, above all, his understanding of patriotic and national duties, as a Pole fighting for his country’s independence and as a deportee to Siberia.